2020
DOI: 10.7759/cureus.6722
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Hyperuricemia in Patients with Acute Myocardial Infarction – A Case-Control Study

Abstract: Introduction Various researches have stated the correlation between serum uric acid (sUA) and cardiovascular disease (CVD); however, no local studies are available. In this study, we will determine the prevalence of hyperuricemia in patients with acute myocardial infarction and compare with the control group. Methods This case-control study was conducted from March to November 2019 in the tertiary care hospital in Pakistan. In all, 119 patients with acute myocardial infarction were enrolled in this study, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…A population study based on big data showed that from 2014 to 2017, the prevalence rate of HUA in Chinese adults increased from 18.29 to 23.06% 3 . At present, there were many studies to show that HUA is positively correlated with hypertension 4 , diabetes 5 , metabolic syndrome 6 , acute myocardial infarction 7 , coronary heart disease 8 , acute kidney injury 9 , chronic kidney disease 10 , high incidence of cancer and mortality 11 . However, there is still a lack of evidence on whether lowering uric acid can improve the prognosis of related diseases 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…A population study based on big data showed that from 2014 to 2017, the prevalence rate of HUA in Chinese adults increased from 18.29 to 23.06% 3 . At present, there were many studies to show that HUA is positively correlated with hypertension 4 , diabetes 5 , metabolic syndrome 6 , acute myocardial infarction 7 , coronary heart disease 8 , acute kidney injury 9 , chronic kidney disease 10 , high incidence of cancer and mortality 11 . However, there is still a lack of evidence on whether lowering uric acid can improve the prognosis of related diseases 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Elevated concentrations of UA not only lead to the deposition of sodium urate crystals in periarticular tissues, but also within the walls of blood vessels, and the presence of these deposits in the blood vessel walls has the consequence of the presence of these deposits in the vascular wall is damage to the vascular endothelium, which promotes atherosclerotic lesions and leads to the development of ACS. In a recent study [16] from Pakistan, it was confirmed that in patients with AMI, SUA levels were higher in the test group than in the control group and the number of patients with HUA was also higher than in the control group. HUA has been linked to the development of other diseases which are known risk factors for ACS such as hypertension, dyslipidemia, obesity, metabolic syndrome and chronic kidney disease.…”
Section: Discussionmentioning
confidence: 82%
“…The patients with myocardial infarction exhibited significantly elevated uric acid levels compared to the control group (p<0.001). A case-control study conducted by Mal et al [17] found that, out of 200 people, 80 patients (about 40%) with acute myocardial infarction had hyperuricemia, which is characterized by very high uric acid levels in the bloodstream. The incidence of hyperuricemia in the control group (n=200) without acute myocardial infarction was 25% (n=50) (p<0.05).…”
Section: Discussionmentioning
confidence: 99%